Eco-innovation by Integrating Biomimetic Design and ARIZ - Chen, Wang-Chih; Chen, Jahau Lewis (Procedia CIRP, 2014)
This work presents a new eco-innovative biomimetic design tool by integrating the algorithm for inventive problem solving (Russian acronym: ARIZ) with biologically significant vocabularies to search for related biological cases. ARIZ includes a complete procedure for analyzing problem model and related resources, resolving conflicts and generating solutions. This tool searches for biological key words by using the Noun1-Noun2-Verb model in replace of the Su-Field model for analyzing system conflicts and finds related biological cases. Analyzing these biological cases and available resources helps designers to design eco-products based on biomimetic concepts. An example is used to demonstrate the capability of the proposed method.